Developing a Digital Cultural Flipbook to Enhance Understanding Concept of Diversity and Tolerance - Nugraheni, Dian; Wuri Wuryandani; Purnomo; Agus Purwanto (Universitas Pendidikan Ganesha, 2025)
Instilling tolerance through learning about cultural diversity remains a challenge due to its abstract nature for students, so technology-based learning media that can attract their attention and increase their engagement is needed. This study aims to develop and test the feasibility, practicality, and effectiveness of digital flipbook learning media containing cultural diversity in improving students' understanding and tolerance. This research is a research and development (R&D) study using the ADDIE model. The research subjects include 186 students and 7 fourth-grade elementary school teachers. Data were collected through interviews, observations, needs assessments, product validation, response questionnaires, comprehension tests, and tolerance character scales. Data analysis was conducted using descriptive quantitative methods and through paired sample t-tests, independent sample t-tests, and MANOVA. Validation results indicated that the media is highly suitable for use (subject matter experts = 85.2%; media experts = 95%). The media was deemed practical based on student and educator responses, with the highest score reaching the “very practical” category. Effectiveness tests showed significant differences in comprehension scores and tolerance character before and after using the digital flipbook (p < 0.005). MANOVA tests also indicated significant differences between the experimental and control groups simultaneously. Thus, the culturally-infused digital flipbook was proven effective in enhancing comprehension and fostering tolerance character, and is suitable for use as an innovative learning medium in elementary schools.